The double round-robin population unravels the genetic architecture of grain size in barley. (12th September 2022) - Shrestha, Asis; Cosenza, Francesco; van Inghelandt, Delphine; Wu, Po-Ya; Li, Jinquan; Casale, Federico A; Weisweiler, Marius; Stich, Benjamin
Abstract: Grain number, size and weight primarily determine the yield of barley. Although the genes regulating grain number are well studied in barley, the genetic loci and the causal gene for sink capacity are poorly understood. Therefore, the primary objective of our work was to dissect the genetic architecture of grain size and weight in barley. We used a multi-parent population developed from a genetic cross between 23 diverse barley inbreds in a double round-robin design. Seed size-related parameters such as grain length, grain width, grain area and thousand-grain weight were evaluated in the HvDRR population comprising 45 recombinant inbred line sub-populations. We found significant genotypic variation for all seed size characteristics, and observed 84% or higher heritability across four environments. The quantitative trait locus (QTL) detection results indicate that the genetic architecture of grain size is more complex than previously reported. In addition, both cultivars and landraces contributed positive alleles at grain size QTLs. Candidate genes identified using genome-wide variant calling data for all parental inbred lines indicated overlapping and potential novel regulators of grain size in cereals. Furthermore, our results indicated that sink capacity was the primary determinant of grain weight in barley. Abstract : Multi-parent population has uncovered a natural allelic series across quantitative trait loci associated with grain size and weight that will contribute to identifying causal genes and yield improvement in barley.